Actividad física y autoconcepto físico en estudiantes de la carrera profesional de Educación Física, Facultad de Ciencias de la Educación Y Humanidades, UNAP 2021 - Nacimento Rubio, Josimar (2025)
The relationship between physical activity and physical self-concept in physical education students is established quantitatively and correlationally, with a non experimental, correlational, and cross-sectional design. For physical self-concept, a Likert scale with 11 dimensions and 40 questions was used, and for physical activity, a questionnaire with 5 dimensions of 11 items was applied. Regarding self-concept: 40.7% good, 35.6% very good, 20.3% fair, and 3.4% poor; and for physical activity, 69.5% fair, 23.7% good, and 6.8% poor. Physical activity and health improvements were highly and significantly positive; self-concept evaluation was moderately and significantly positive; athletic competence evaluation was moderately and significantly positive; strength compensation was moderately and significantly positive; and appearance compensation was not significant.